1984
DOI: 10.1093/ajcn/39.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Liver concentrations of vitamin A and carotenoids, as a function of age and other parameters, of American children who died of various causes

Abstract: To assess the age-dependent vitamin A status of children, liver samples taken at autopsy from 170 American children 0-15 yr of age were analyzed for vitamin A and carotenoids. The median liver vitamin A concentration at birth was low (11 micrograms retinol/g), remained constant to 3 mo, rapidly increased to 4 yr (130 micrograms/g) and then remained constant into adolescence. In contrast the vitamin A status of premature infants deteriorated after birth. Of infants less than 3 mo, approximately one-fourth and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
6

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 13 publications
3
42
0
6
Order By: Relevance
“…Some investigators have questioned the use of 0.70 mmol/l as the cutoff point indicating the presence of VAD in young infants (Lindblad et al, 1998;Bhaskaram et al, 2000;Schmidt et al, 2001, de Pee andDary, 2002), and have proposed a value of 0.35 mmol/l as the limit (Lindblad et al, 1998). It is known that babies are born with low hepatic reserves of vitamin A, showing retinol levels up to 50% lower than those of their mothers (Olson et al, 1984;Haskell and Brown, 1999;Azais-Braesco and Pascal, 2000). In addition, owing to immaturity of the gastrointestinal tract, vitamin A absorption may be less efficient in infants younger than 6 months than in adults and circulating retinol levels p0.70 mmol/l are common, even in well-nourished populations (Haskell and Brown, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have questioned the use of 0.70 mmol/l as the cutoff point indicating the presence of VAD in young infants (Lindblad et al, 1998;Bhaskaram et al, 2000;Schmidt et al, 2001, de Pee andDary, 2002), and have proposed a value of 0.35 mmol/l as the limit (Lindblad et al, 1998). It is known that babies are born with low hepatic reserves of vitamin A, showing retinol levels up to 50% lower than those of their mothers (Olson et al, 1984;Haskell and Brown, 1999;Azais-Braesco and Pascal, 2000). In addition, owing to immaturity of the gastrointestinal tract, vitamin A absorption may be less efficient in infants younger than 6 months than in adults and circulating retinol levels p0.70 mmol/l are common, even in well-nourished populations (Haskell and Brown, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although quantitation of hepatic stores of vitamin A is considered an accurate way of measuring vitamin A status, the presence of portal tract expansion and fibrosis may artificially reduce vitamin A content of the liver when calculated on a per liver weight basis. 42 In addition, autopsy studies have demonstrated that needle biopsies from different parts of the liver yield vastly different vitamin A concentrations. 43 Because of these difficulties in interpreting vitamin A stores directly in liver specimens, we believe the functional test of vitamin A reserves, the RDR, 15,16 is a more accurate (and certainly more feasible) means of assessing vitamin A status in the presence of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on surveys of victims of accidental death, an acceptable range of vitamin A in the normal adult human liver is 100-300 pg/g of tissue (9). The liver vitamin A concentrations in children vary markedly with age, being low during infancy relative to later childhood, adolescence, and young adulthood (10,11). In children, a liver vitamin A concentration <40 pg/g is generally considered to be indicative of low vitamin A reserve, and <20 pg/g is considered as marginal or poor (4,10,11).…”
Section: Methodsmentioning
confidence: 99%